Reliability and Degradation Mechanisms in High Power Broad-Area InGaAs-AlGaAs Strained Quantum Well Lasers. Issue 1792 (28th May 2015) - Sin, Yongkun; Presser, Nathan; LaLumondiere, Stephen; Brodie, Miles; Lingley, Zachary; Ives, Neil; Foran, Brendan; Lotshaw, William; Moss, Steven C.
ABSTRACT: Reliability and degradation processes in broad-area InGaAs-AlGaAs strained quantum well (QW) lasers are under intensive investigation because these lasers are the key components for fiber lasers and amplifiers that have found both industrial and military applications in recent years. Unlike single-mode lasers that were developed for high reliability telecom applications, broad-area lasers were mainly targeted for applications that require less stringent reliability of the lasers until recently. Especially, the lack of field reliability data is a concern for satellite communication systems where high reliability is required of lasers for long-term duration. For our present study, we addressed this concern by performing long-term life-tests of broad-area InGaAs-AlGaAs strained QW lasers and also by studying mechanisms that are responsible for catastrophic degradation of the lasers.